Vulnerabilidades em pessoas idosas e repercussões da pandemia por Covid-19: estudo de método misto - Both, Caroline Thaís (2023)
The aging process is accompanied by a set of biopsychosocial changes that can impact the maintenance of functional capacity and independence in older people and predispose them to adverse social and health outcomes. It is inferred that the Covid-19 pandemic represented a unique and significant context of exposure to vulnerable situations. The objective was to analyze situations of vulnerability in elderly people and the repercussions caused by the Covid-19 pandemic in the space of Primary Health Care. This is a mixed method study, with a sequential explanatory strategy (QUANT-qual), carried out with elderly people in Primary Health Care in Coronel Bicaco, an adjacent rural municipality located in the northwest region of Rio Grande do Sul, Brazil. The quantitative stage had 356 participants, took place between January and June 2023. The following instruments were applied: sociodemographic characterization and health conditions; Clinical-Functional Vulnerability Index (IVCF-20); Geriatrics Depression Scale 15 (GDS-15); and Hwalek-Sengstock Elder Abuse Screening Test (H-S/EAST). Statistical and descriptive analysis was carried out, Pearson's chi-square test and Kruskal-Wallis test. The qualitative investigation took place between July and August 2023, with 22 elderly people participating. Data were collected through narrative interviews and analyzed according to the precepts of thematic content analysis. The results were integrated/mixed during the analysis, interpretation and discussion of the data. The average age of the participants was 71.3 years. The majority were female, with low education, low monthly income, presence of comorbidities and were constantly taking medications. Elderly people experience situations of individual, social and pragmatic vulnerability, in which 163 (45.4%) presented a medium to high risk of clinical-functional vulnerability, 57 (17.9%) had mild or severe depression and 63 ( 17.7%) risk of suffering violence. Among the main factors that contribute to vulnerabilities are advanced age, low education, worse self-perception of health, presence of comorbidities, continuous use of medications, greater number of accesses to health services and psychological changes in the last year. Elderly people also experience the repercussions caused by the Covid-19 pandemic, mainly on health conditions, such as depression and organic changes. It was identified that there is an interface between the dimensions of vulnerabilities and these are associated with the repercussions of the Covid-19 pandemic. Individual vulnerabilities overlap and interfere with the social and pragmatic dimensions, but these are also mutually influenced, demonstrating their interdependence in the daily lives of elderly people. It was evident that conditions of individual and social vulnerability can influence the search for and access to health services by the elderly population. This aspect signals that primary care professionals must carry out an interdisciplinary and multisectoral approach and direct a special focus on this population segment, so that integrated and longitudinal interventions and care can be successful.